Differential A1/A2 β-casein (CSN2) gene-derived allelic and genotypic frequencies across Ecuadorian exotic dairy cattle breeds - Luis F. Cartuche-Macas; Luis F. Cartuche-Macas; Jorge F. Navarrete-Mera; Miguel A. Gutiérrez-Reinoso; Miguel A. Gutiérrez-Reinoso; Manuel García-Herreros; Manuel García-Herreros (Frontiers in Veterinary Science)
Recently, a growing interest in dairy cattle selection has been triggered due to specific genetic variations of the β-casein (CSN2) gene which was associated to several human disorders. The aim of the present study was to evaluate the A1/A2 β-casein (CSN2) gene-derived allelic and genotypic frequencies in five Ecuadorian dairy cattle breeds to determine the genetic diversity of the A1/A2 β-casein locus. Genomic Deoxyribonucleic Acid (gDNA) was extracted from hair samples collected from different dairy cattle breeds, namely Holstein Friesian (HF), Brown Swiss (BS), Jersey (J), Gyr (G), and crossbreds (CB) raised commonly in seven different regions in order to identify A1 and A2 variants. Genomic determination of the β-casein (CSN2) gene variants was carried out evaluating the Exon 7 region in order to identify and confirm the accuracy of the A1/A2 β-casein (CSN2) gene-derived polymorphisms related to the genotypes and the allelic profiling. A2 allele frequencies were determined as 0.628, 0.643, 0.727, and 0.644 in HF, BS, J, and CB, respectively. In contrast, the lowest A1 allele frequency (0.145) as well as the greatest A2 allele frequency (0.855) was detected in G. No significant differences for allelic frequency were observed among breeds (p > 0.05). Homozygous A1 genotype frequency in HF, BS, J, and CB was 0.140, 0.110, 0.050 and 0.150, respectively. Interestingly, the A1A1 genotype was absent in G (p < 0.05). A1A2 genotypes were 0.290, 0.490, 0.450, 0.290, and 0.420 in HF, BS, J, G, and CB, respectively. Finally, the A2A2 genotype was 0.400, 0.400, 0.500, and 0.460 in HF, BS, J, and CB, respectively. However, the greatest A2A2 genotype frequency was observed in G (0.710). No deviation from the Hardy–Weinberg equilibrium was found in any breed in terms of β-casein gene (p > 0.05). Moreover, the results revealed a geographically related distribution of A1/A2 allele and genotype frequencies of β-casein (CSN2) gene. In terms of genetic diversity a differential distribution of heterozygosity was observed among breeds being average Ho, He, uHe, and F values determined as 0.429, 0.438, 0.439, and 0.022, respectively. In conclusion, the β-casein (CSN2) gene was polymorphic in all the cattle breeds analyzed. The A1/A2 allele and genotype frequencies varied depending on the breed and the geographic region which may be conditioned by the specificities related to different breeding selection programmes. A2 allele and A2A2 genotype frequency were particularly greater in Gyr cattle which have a great potential for A2 milk production without compromising genetic diversity.